Hungry people cannot take care of their future: impact of hunger on intertemporal choice. Issue 3 (17th December 2019) - Lu, Wei; Zhou, Yuwei; Pan, Li Sunny; Zhao, Yuhao
Abstract : Purpose: People often need to make intertemporal choices in their daily life, such as savings and spending, but their decisions are not always entirely rational. The purpose of this paper is to study the effect of hunger on intertemporal choices and the moderating effect of sensitivity to reward. Design/methodology/approach: Two studies verified these two hypotheses. The first study confirmed the existence of the main effect by manipulating food aroma. In the second study, by manipulating hunger with images, the authors increased external validity of the study and confirmed the regulation of the sensitivity of rewards. Findings: The authors found that hungry people prefer to reap the benefits as early as possible in an intertemporal choice; this effect is significant only for those people who are sensitive to reward. Practical implications: The research contributes to understand more about which factors will influence Chinese residents' decisions on savings and spending. It also has practical implication for government policy, for example, proposing new ideas for reducing household savings rate and stimulating consumption. Originality/value: The results confirmed that hunger significantly affects consumers' intertemporal choices, which broadened the scope of researches on the factors that influence intertemporal choice, and advanced the study on the influence of individual's physiological state on intertemporal choices. This study filled the gaps in previous researches, and opened up new research ideas for interdisciplinary study.